Making history come alive: Seeking truth and justice: An interview with Vijaya Teelock - Vijaya Teelock; David Denborough (International Journal of Narrative Therapy and Community Work)
In this interview, Mauritian historian Vijaya Teelock discusses breaking historical silences, democratising history, intangible heritage, memorialising and the complexities of seeking justice and reparation for historical wrongs. The interview took place in Vijaya’s home in Mauritius with David Denborough, Cheryl White and Diana Shanto present.